Synthesis and pharmacological evaluation of bivalent tethered ligands to target the mGlu2/4 heterodimeric receptor results in a compound with mGlu2/2 homodimer selectivity. Issue 13 (1st July 2020) - Fulton, Mark G.; Loch, Matthew T.; Rodriguez, Alice L.; Lin, Xin; Javitch, Jonathan A.; Conn, P. Jeffrey; Niswender, Colleen M.; Lindsley, Craig W.
Graphical abstract: Highlights: Detailed SAR of tethered PAM ligands targeting the mGlu2/4 heterodimer. When DCG-IV and L-AP4 agonists are combined, 14d can potentiate the mGlu2/4 heterodimer. Large, tethered ligands can access PAM site and potentiate homodimers. Abstract: This Letter details our ongoing efforts to develop selective positive allosteric modulators (PAMs) of the mGlu2/4 heterodimeric receptor that exists in the CNS and may represent a novel drug target to modulate the glutamatergic system. As multiple hit-to-lead campaigns from HTS hits failed to produce selective small molecule mGlu2/4 heterodimer PAMs, we were inspired by the work of Portoghese to synthesize and evaluate a set of nine bivalent tethered ligands (possessing an mGlu2 PAM at one terminus and an mGlu4 PAM at the other). Utilizing G protein-Inwardly Rectifying Potassium (GIRK) channel functional assays, we found that the tethered ligands displayed PAM activity in a cell line co-expressing both mGlu2 and mGlu4 but also in cells expressing mGlu2 or mGlu4 alone. In a CODA-RET assay, one of the tethered ligands potentiated mGlu2/4 heterodimers; however, another compound displayed 75-fold preference for the mGlu2/2 homodimer over heterodimeric mGlu2/4 or homomeric mGlu4/4 . This work highlights the development of mGlu receptor PAMs with homodimer/heterodimer preference and expands the potential for PAMs as tethered ligands beyond the more classical antagonists and NAMs.